Cultura organizacional e comprometimento no trabalho em hospitais públicos de Minas Gerais - Isabella do Couto Reis (2015)
This study identified and analyzed how the organizational culture has influenced the organizational commitment of the servers in two public hospitals in Minas Gerais Ômega Hospital and Sigma Hospital. The goal was identifying cultural profiles associated to the organizational commitment. To do so, a survey was conducted based on the Organizational Culture Assessment Instrument (OCAI) of Cameron and Quinn (2011) and the Model of Three Dimensions of Meyer e Allen (1997). The sample is constituted of assistance and administrative servers, totaling 125 participants in the Ômega Hospital and 248 servers in the Sigma Hospital. In this last one, both, militaries and civil answered the questionnaire. The results of variance analysis indicate that the dominant culture in the hospitals are the hierarchy and clan cultures. Besides this, analyzes of variance shown that are subcultures in the hospitals. The Ômega Hospital has a mix of hierarchy (to assistance and administrative servers) and clan (to assistance servers) cultures with some aspects of market culture (to administrative servers). The Sigma Hospital culture presented prevailing traits of hierarchy (to civil and militaries assistance servers) and clan cultures (to all servers). The results shown that the servers in the hospitals are most committed affectively. Although, the descriptive analyzes demonstrated that the civil servers are committed for reasons of continuance. This is contrary to the organizational commitment literature. The regression analysis identified the clan and adhocracy culture influence the commitment positively; the hierarchy culture influences sometimes positively, sometimes negatively; and the market culture does not influences the servers link with the organization. Some of the study limitations is not to approach the servers of night shift and the reduced samples of administrative servers in both hospitals. It is recommended news searches in this format and in the public hospitals context to better identify the market culture behavior. Besides this, it is relevant working the organizational culture and commitment with another theme, like job satisfaction, stress, personnel and organizational identity, involving both quantitative and qualitative methods.